A construção da legitimidade das agências de rating de crédito no Brasil - Vale, Miriam Pires Eustachio de Medeiros (2016)
This research deals with legitimacy, status and reputation of credit rating agencies in Brazil starting from the view of its audience. Field research was conducted with the audience of the following organizations: Argus Classification of Credit Risk, Austin Rating, Fitch Ratings Brazil, Liberum Ratings, Moody's, SR Rating and Standard & Poor's (S & P). We interviewed more than forty market agents in-depth to understand how the phenomenon of credit rating agencies in Brazil can be explained, as well as the role of legitimacy, status and reputation of these companies. The issue in question is important because is current and stimulates discussion about how interorganizational relationships affect the view of the audience, bringing it closer to the area of Organizational Studies. The main objective is to understand the process through which these organizations become legitimate and start deserving the trust of its audience. Therefore, we researched the relationship of credit rating agencies not only with its customers but also with market players that influence the hiring of these agencies. The interviews were transcribed and coded using ATLAS.ti software. From the coding, some concepts were extracted in order to explain the phenomenon of credit rating agencies in Brazil. Surprisingly, the regulation is not the main reason to contract a credit rating agency. The contractors are worried about their fundraising, which demonstrates that the clients of the credit rating agencies are more concerned with the acceptance of their emissions on the market by investors. The agencies, in this scenario, are a kind of information middleman among financial actors, providing a 'seal of approval' for investors who feel more comfortable and safe in investing in emissions that have already been assessed by the agencies. When the fieldwork came to investors, it was interesting to notice that what was happening was a kind of outsourcing because the investment decision was taken based on the assessments made by the credit rating agencies. The financial actors who make this try to exempt themselves from liability if something wrong happens, this attitude is known as 'cover my ass'. However, the agencies deny that this may occur in their disclaimers. It is unanimous among respondents that there are two agencies groups: international and national, it is clear that there is status differentiation between them, with American agencies occupying the highest status. For the respondents, US agencies have something differential, which is called 'plaque' and the interviewees outline what national agencies should do to try to reach the same level. Completing the survey, we see that in Brazil, the agencies do not play the same role they have in other markets and that the legitimacy of them directly depend on the acceptance of their ratings by investors.